Flower-like ZnO sacrificial zinc source assisted ZIF-8 derived electrode material and preparation method thereof
Patent Information
- Application Number
- CN202611513424.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-28
- Publication Date
- 2026-10-30
AI Technical Summary
[0003]然而,直接碳化ZIF-8存在以下关键问题:ZIF-8的有机配体(2-甲基咪唑)在高温(>500°C)分解过程中,骨架中的锌元素会以金属锌或氧化锌的形式大量挥发流失,导致活性位点损失、孔结构坍塌和电化学性能下降
本发明提供了花状ZnO牺牲锌源辅助的ZIF-8衍生电极材料及其制备方法,具体包括碳布基底、负载于碳布表面的花状氧化锌三维骨架、以及包覆于所述花状氧化锌骨架表面的ZIF-8衍生的无定形碳/氧化锌复合层,所述无定形碳/氧化锌复合层与花状氧化锌骨架形成分级结构。本发明通过在ZIF-8碳化前预先在碳布基底上电沉积花状氧化锌,使该氧化锌在后续碳化过程中同时充当结构骨架和锌保留源(牺牲锌源),从而有效抑制ZIF-8分解过程中锌的挥发损失,制备得到电化学性能优异的复合电极材料。
Smart Images

Figure CN123008941A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electrochemical sensing materials technology, and provides a ZIF-8 derived electrode material assisted by a flower-shaped ZnO sacrificial zinc source and its preparation method. Background Technology
[0002] Electrochemical sensors are widely used in food, environmental, and biological detection fields due to their advantages such as high sensitivity, fast response speed, and ease of miniaturization. ZIF-8 (Zeolitic Imidazolate Framework-8) is a typical metal-organic framework (MOF) material formed by the coordination of zinc ions and 2-methylimidazolium. It has a high specific surface area, tunable pore structure, abundant nitrogen content, and uniformly distributed active sites. The derivative material obtained by carbonizing ZIF-8 in a high-temperature inert atmosphere (carbonized ZIF-8, CZIF-8) exhibits excellent performance in the field of electrocatalysis due to the zinc oxide nanoparticles embedded in its carbon matrix and its nitrogen-doped porous structure.
[0003] However, direct carbonization of ZIF-8 presents the following key problem: During the decomposition of the organic ligand (2-methylimidazole) of ZIF-8 at high temperatures (>500°C), a large amount of zinc in the framework volatilizes and is lost in the form of metallic zinc or zinc oxide, leading to the loss of active sites, collapse of the pore structure, and a decline in electrochemical performance. This zinc volatilization problem severely limits the practical application of ZIF-8-derived materials in electrochemical sensors.
[0004] Existing improvement methods mainly include: (1) carbonization under an inert atmosphere, but it is still difficult to completely suppress zinc volatilization loss; (2) using bimetallic sources (such as Cu-MOF@ZIF-8, Au / ZIF-8) to form a core-shell structure, but this increases the complexity and cost of the process, and often introduces noble metal catalysts; (3) pre-doping other metals into the ZIF-8 structure to stabilize zinc species, but none of these methods can fundamentally solve the problem of zinc volatilization during high-temperature carbonization.
[0005] Furthermore, existing electrochemical sensors mostly use noble metals (such as gold, platinum, and palladium) as electrocatalysts. Although these offer high sensitivity, they are expensive, and the metal precursors are environmentally unfriendly, making it difficult to meet the development needs of green analytical chemistry. Constructing high-performance electrochemical sensors without noble metals on flexible substrates (such as carbon cloth) remains a challenge.
[0006] In the prior art, ZnO / ZIF-8 core-shell structures and their carbon cloth-based composite materials have been reported. For example, Chinese patent CN114497475A discloses a lithium-ion battery anode material with ZnO nanoparticles as the core and ZIF-8 carbonized framework as the shell; Cao et al. disclosed a flexible supercapacitor electrode with hollow core-shell ZnO@ZIF-8 on carbon cloth in Chemical Communications (2019, 55, 1746). Chinese patent CN117269271A discloses an electrochemically self-supporting modified electrode for detecting nitrite in food, which electrodeposits nano-flower-shaped zinc oxide on the surface of plasma-treated carbon cloth, and loads gold onto the surface of the flower-shaped zinc oxide by magnetron sputtering to achieve highly sensitive detection. However, the above-mentioned solutions either apply them to energy storage electrode materials, or use hydrothermal or seed methods to grow ZnO, or still require magnetron sputtering with precious metals (such as Au) to obtain high catalytic activity. Their carbonization temperatures are all high, and none of them address the problem of zinc volatilization loss during the carbonization process of ZIF-8, nor do they use them as electrochemical sensing electrodes without precious metals.
[0007] In addition, another type of technology constructs a hollow carbon structure by volatilizing zinc species at high temperatures (e.g., carbonizing zinc at temperatures above 800°C to create pores through evaporation). This technology is contrary to the concept of this application and cannot preserve the active sites of ZnO.
[0008] Therefore, there is an urgent need to develop a novel composite electrode material that can effectively suppress zinc volatilization loss during the carbonization process of ZIF-8 and does not require the use of precious metal precursors, as well as a simple preparation method thereof. Summary of the Invention
[0009] In view of this, the purpose of the present invention is to provide a ZIF-8 derived electrode material assisted by a flower-shaped ZnO sacrificial zinc source and a method for preparing the same.
[0010] To achieve the above objectives, the present invention provides the following technical solution: 1. A ZIF-8 derived electrode material assisted by a flower-shaped ZnO sacrificial zinc source, comprising a carbon cloth substrate, a flower-shaped zinc oxide three-dimensional framework loaded on the surface of the carbon cloth, and a ZIF-8 derived amorphous carbon / zinc oxide composite layer covering the surface of the flower-shaped zinc oxide framework, wherein the amorphous carbon / zinc oxide composite layer and the flower-shaped zinc oxide framework form a hierarchical structure.
[0011] 2. The preparation method of the aforementioned flower-shaped ZnO sacrificial zinc source-assisted ZIF-8 derived electrode material includes the following steps: S1. Carbon cloth pretreatment: Clean the carbon cloth, dry it, and treat it with low-temperature plasma to obtain hydrophilic carbon cloth PT-CC; S2. Electrodeposition of flower-shaped zinc oxide: Using PT-CC as the working electrode, cathodic electrodeposition occurs in an electrolyte containing Zn(NO3)2·6H2O and KCl. KCl acts as a morphology guiding agent to induce the formation of flower-shaped zinc oxide structure, resulting in carbon cloth ZnO@CC with flower-shaped zinc oxide grown on the surface. S3. In-situ growth of ZIF-8: Using ZnO@CC as the working electrode, cathodic electrodeposition occurs in an electrolyte containing 2-methylimidazole and Zn(NO3)2·6H2O, and ZIF-8 is grown in-situ on the flower-shaped zinc oxide surface to obtain ZIF-8 / ZnO@CC. S4. Carbonization treatment: Under an inert atmosphere, ZIF-8 / ZnO@CC is heated to 500°C and carbonized to obtain the composite electrode material CZIF-8 / ZnO@CC.
[0012] Preferably, in step S1, the cleaning includes: ultrasonic cleaning with deionized water, anhydrous ethanol, and deionized water for 5 to 15 minutes each, more preferably 10 minutes.
[0013] Preferably, in step S1, the process conditions for low-temperature plasma cleaning are: 60 Pa vacuum and 0.5 cm electrode spacing for 40 minutes.
[0014] Preferably, in step S2, an Ag / AgCl electrode is used as the reference electrode and a platinum electrode is used as the counter electrode; the electrolyte in step S2 contains 2.5 mM Zn(NO3)2·6H2O and 5 mM KCl; cathodic electrodeposition is performed at a constant potential of -1.1 V (vs. Ag / AgCl); the electrodeposition time is 300 s and the electrolyte temperature is 50 °C.
[0015] Preferably, in step S3, an Ag / AgCl electrode is used as the reference electrode and a platinum electrode is used as the counter electrode; the electrolyte in step S3 contains 0.4 M 2-methylimidazole and 0.05 M Zn(NO3)2·6H2O; cathodic electrodeposition is performed at a constant potential of -1.1 V (vs. Ag / AgCl); the electrodeposition time is 30 minutes, and the electrolyte temperature is room temperature.
[0016] Preferably, in step S4, the heating rate is 5°C / min and the carbonization time is 30 minutes.
[0017] Preferably, in step S4, the inert atmosphere is nitrogen or argon.
[0018] 3. Application of the aforementioned flower-shaped ZnO sacrificial zinc source-assisted ZIF-8 derived electrode material as a working electrode in electrochemical sensors.
[0019] 4. An electrochemical sensor comprising a ZIF-8 derived electrode material assisted by the aforementioned flower-shaped ZnO sacrificial zinc source as a working electrode.
[0020] Preferably, the electrochemical sensor includes a working electrode, a reference electrode, and a counter electrode, which are arranged in parallel on the inner wall of the tubular cavity and connected by conductive copper foil.
[0021] More preferably, the reference electrode is Ag / AgCl@CC, and the counter electrode is bare carbon cloth.
[0022] 5. Application of the aforementioned electrochemical sensors in the detection of nitrite and / or sulfite in food or tap water.
[0023] Preferably, the food includes, but is not limited to: sausage, kimchi, and milk.
[0024] 6. A method for electrochemically detecting nitrite and / or sulfite in food or tap water, based on the aforementioned electrochemical sensor, using cyclic voltammetry, amperometric current-time method, or differential pulse voltammetry.
[0025] The beneficial effects of this invention are: This invention provides a ZIF-8 derived electrode material assisted by a flower-shaped ZnO sacrificial zinc source and its preparation method. Specifically, it includes a carbon cloth substrate, a flower-shaped zinc oxide three-dimensional framework loaded on the carbon cloth surface, and a ZIF-8 derived amorphous carbon / zinc oxide composite layer coating the surface of the flower-shaped zinc oxide framework. The amorphous carbon / zinc oxide composite layer and the flower-shaped zinc oxide framework form a hierarchical structure. This invention pre-deposits flower-shaped zinc oxide on the carbon cloth substrate before ZIF-8 carbonization, allowing this zinc oxide to simultaneously act as a structural framework and a zinc retention source (sacrificial zinc source) during subsequent carbonization, thereby effectively suppressing zinc volatilization loss during ZIF-8 decomposition and preparing a composite electrode material with excellent electrochemical performance.
[0026] The preparation method of the electrode material of this invention mainly includes the following steps: carbon cloth pretreatment; electrodeposition of flower-shaped zinc oxide on the surface of the pretreated carbon cloth; in-situ growth of ZIF-8 on the surface of the flower-shaped zinc oxide; and carbonization treatment under an inert atmosphere to obtain the composite electrode material. This invention utilizes the pre-deposited flower-shaped zinc oxide, which simultaneously acts as a structural framework and zinc retention source during the carbonization process, thus advancing the decomposition temperature of the ZIF-8 organic ligand to 300–400°C. This allows carbonization to be completed within a temperature range below the zinc volatilization initiation temperature, effectively suppressing zinc volatilization loss, retaining more ZnO active sites, and significantly increasing the electrochemical active area of the composite material (EASA reaches 4.48 cm²). 2The carbonization product contains zinc in the form of hexagonal wurtzite ZnO, which exhibits a Zn-O lattice oxygen characteristic peak at 531.0 eV in its O1s spectrum. The CZIF-8 / ZnO@CC composite electrode material prepared in this invention does not require any noble metal (Au, Pt, Pd, etc.) precursors and exhibits excellent electrochemical detection performance for both nitrite and sulfite (detection limits are 0.24 μM and 0.52 μM, respectively). It can be applied to portable electrochemical sensors to achieve rapid on-site detection of food samples.
[0027] Specifically, the present invention has the following advantages: (1) By using flower-shaped zinc oxide as a structural framework and zinc retention source, the main decomposition temperature of ZIF-8 organic ligands is advanced by about 100-260°C (from 500-560°C to 300-400°C). Carbonization can be completed at a lower temperature, effectively suppressing the volatilization loss of zinc during high-temperature carbonization and preserving more ZnO active sites and pore structure integrity.
[0028] (2) The flower-like zinc oxide also serves as a three-dimensional structural framework, which can prevent the aggregation of ZIF-8 particles and significantly increase the electrochemical active area of the composite electrode (EASA reaches 4.48 cm²). 2 3.55 cm higher than CZIF-8@CC 2 ).
[0029] (3) The preparation process of this composite electrode material does not require the use of any precious metal (Au, Pt, Pd, etc.) precursors, the raw material cost is low, the process is environmentally friendly, and it conforms to the concept of green analytical chemistry.
[0030] (4) The obtained CZIF-8 / ZnO@CC composite electrode has excellent electrochemical detection performance for both nitrite and sulfite, with high sensitivity, low detection limit (0.24 μM for nitrite and 0.52 μM for sulfite), and fast response (<2 s to reach steady state).
[0031] (5) It can be used as a working electrode in portable electrochemical sensors to realize the rapid on-site detection of nitrite and sulfite in food (sausage, kimchi, milk, etc.) or tap water.
[0032] Other advantages, objectives, and features of the invention will be set forth in part in the description which follows, and in part will be apparent to those skilled in the art from the following examination, or may be learned from practice of the invention. The objectives and other advantages of the invention can be realized and obtained through the following description. Attached Figure Description
[0033] To make the objectives, technical solutions, and advantages of the present invention clearer, the preferred embodiments of the present invention will be described in detail below with reference to the accompanying drawings, wherein: Figure 1 This is a schematic diagram of the synthesis process of the method of the present invention; the diagram shows the process of preparing CZIF-8 / ZnO@CC by electrodeposition of flower-shaped ZnO, in-situ growth of ZIF-8, and carbonization at 500°C.
[0034] Figure 2 These are scanning electron microscope images of the composite electrode material (CZIF-8 / ZnO@CC) of the present invention at different magnifications, showing the hierarchical structure of the flower-shaped zinc oxide skeleton surface covered with ZIF-8 derived carbon layers; wherein, (b) and (c) are low-magnification SEM images, showing the overall distribution of flower-shaped zinc oxide on the carbon fiber surface; (d) and (e) are high-magnification SEM images, showing the details of the hierarchical structure of the flower-shaped zinc oxide skeleton surface covered with ZIF-8 derived carbon layers.
[0035] Figure 3 The image shows the EDS elemental distribution of the composite electrode material of the present invention, which shows that carbon, oxygen, and zinc elements are uniformly distributed on the surface of carbon fibers, confirming the formation of the ZnO / C composite structure. Among them, (f) is the SEM image of the selected area, and (g), (h), and (i) are the surface distribution maps of carbon, oxygen, and zinc elements, respectively, showing that carbon, oxygen, and zinc elements are uniformly distributed on the surface of carbon fibers, confirming the formation of the ZnO / C composite structure.
[0036] Figure 4 The thermogravimetric analysis curves of ZIF-8@CC and ZIF-8 / ZnO@CC under nitrogen atmosphere are compared. It can be seen that the introduction of flower-shaped zinc oxide advances the main decomposition temperature of ZIF-8 to 300-400°C and stably retains zinc species in the form of ZnO.
[0037] Figure 5 The X-ray diffraction patterns of CZIF-8@CC and CZIF-8 / ZnO@CC after carbonization are shown; the nine diffraction peaks correspond to the characteristic crystal planes of hexagonal wurtzite ZnO.
[0038] Figure 6 The high-resolution O 1s X-ray photoelectron spectrum of the carbonized sample is shown; the oxygen composition of the Zn-O lattice at approximately 531.0 eV directly confirms the presence of ZnO in the carbonization product.
[0039] Figure 7 This is a schematic diagram of the portable electrochemical sensing device of the present invention; it shows the assembly, packaging and testing process of the working electrode (WE), reference electrode (RE) and counter electrode (CE).
[0040] Figure 8The it curves (a) and (d) of the CZIF-8 / ZnO@CC electrode for nitrite and sulfite at different voltages. The it curve of the CZIF-8 / ZnO@CC electrode with continuous addition of nitrite at 0.95 V in 0.1 M PBS (pH = 7.5), with the inset showing the electrode's response time (b). Calibration curve of current density versus nitrite concentration (c). The it curve of the CZIF-8 / ZnO@CC electrode with continuous addition of sulfite at 0.50 V in 0.1 M PBS (pH = 7.5), with the inset showing the electrode's response time (e). Calibration curve of current density versus sulfite concentration (f). Detailed Implementation
[0041] The present invention will be further described below with reference to the accompanying drawings and embodiments. It should be noted that the following description is only for explaining the present invention and does not limit its content.
[0042] Example: Preparation of CZIF-8 / ZnO@CC composite electrode material ( Figure 1 ) S1. Carbon cloth pretreatment: The carbon cloth was cut into 2 cm × 2 cm square pieces, and ultrasonically cleaned with deionized water, anhydrous ethanol, and deionized water for 10 min each, and then vacuum dried at 50°C. The carbon cloth was then placed in a low-temperature plasma device and treated for 40 min under a vacuum of 60 Pa and an electrode spacing of 0.5 cm to obtain hydrophilic carbon cloth (PT-CC).
[0043] S2. Electrodeposition of flower-shaped zinc oxide: Using a PT-CC electrode as the working electrode, an Ag / AgCl electrode as the reference electrode, and a platinum sheet as the counter electrode, the electrolyte was an aqueous solution containing 2.5 mM Zn(NO3)2·6H2O and 5 mM KCl. Electrodeposition was performed at 50°C and a constant potential of -1.1 V (vs. Ag / AgCl) for 300 s. After rinsing with deionized water, the product was dried at 50°C to obtain ZnO@CC.
[0044] In-situ growth of S3 and ZIF-8: ZnO@CC was used as the working electrode, Ag / AgCl as the reference electrode, and a platinum sheet as the counter electrode. The electrolyte was an aqueous solution containing 0.4 M 2-methylimidazole and 0.05 M Zn(NO3)2·6H2O. ZIF-8 / ZnO@CC was obtained by cathodic electrodeposition at a constant potential of -1.1 V (vs. Ag / AgCl) for 30 min at room temperature.
[0045] S4. Carbonization treatment: ZIF-8 / ZnO@CC is placed in a tube furnace and heated from room temperature to 500°C at a rate of 5°C / min under a nitrogen atmosphere, held at that temperature for 30 min, and then naturally cooled to room temperature to obtain CZIF-8 / ZnO@CC composite electrode material. Figure 2 , Figure 3 ).
[0046] Comparative Example: Preparation of CZIF-8@CC control electrode material Except for omitting the flower-shaped ZnO electrodeposition in step S2, the remaining steps are the same as in the example, i.e., PT-CC is directly placed in an aqueous solution containing 0.4 M 2-methylimidazole and 0.05 M Zn(NO3)2·6H2O, and cathodic electrodeposition is performed at a constant potential of -1.1 V (vs. Ag / AgCl) for 30 min to obtain ZIF-8@CC (control sample), which is then carbonized at 500°C under a nitrogen atmosphere to obtain CZIF-8@CC (control sample). Figure 5 , Figure 6 ).
[0047] Experimental Example: Characterization and Performance Testing Thermogravimetric analysis (TGA) Figure 4 The results showed that the main decomposition temperature of the control sample ZIF-8@CC prepared in the comparative example was 500-560°C, significantly higher than the 300-400°C of the example; and its EASA was only 3.55 cm⁻¹. 2 This is lower than the 4.48 cm of the example. 2 The above comparison shows that the pre-deposition of flower-like ZnO can significantly reduce the carbonization decomposition temperature of ZIF-8, inhibit zinc volatilization, and increase the electrochemical active area.
[0048] Regarding the selection of the carbonization temperature range for this invention: Figure 4Two curves were compared: one was the composite precursor ZIF-8 / ZnO@CC from the embodiments of the present invention (first electrodeposited flower-like ZnO and then grown ZIF-8), and the other was the control sample ZIF-8@CC without flower-like ZnO (prepared in the comparative example). The organic ligand (2-methylimidazole) in the control sample only underwent major decomposition at 500-560°C, meaning the ligand only "began" decomposition at the conventional carbonization temperature, and the decomposition process overlapped with the volatilization risk of zinc species in time; while the precursor from the embodiments of the present invention, due to the presence of the pre-deposited flower-like ZnO framework, had its major decomposition temperature of the ligand advanced to 300-400°C, about 100-260°C earlier than the control sample. Because the ligands have already decomposed completely, the TG curve of the precursor of this invention exhibits a nearly horizontal and stable plateau in the 450-600°C range, with almost no further weight loss. This indicates that within this temperature range, the ligands have been completely converted into the derived carbon layer, the carbonization reaction is fully completed, and the zinc species are anchored by the flower-like ZnO framework and stably retained in the form of ZnO without volatilization or loss. In contrast, both curves show significant weight loss again above approximately 700°C, which is the temperature signal at which the zinc species begin to volatilize. Therefore, the lower limit of 450°C ensures that carbonization is completely completed (below this temperature, ligand decomposition is incomplete and the graphitization of the derived carbon layer is insufficient), while the upper limit of 600°C ensures that the operating point is far from the zinc volatilization initiation temperature (>700°C), thus defining a unique and repeatable temperature window between "sufficient carbonization" and "no zinc loss." Among these, the TG curve is most stable and the product has the highest electrochemically active area (4.48 cm²) in the 480-550°C range. 2 Therefore, 500°C is the preferred range, and is the optimal implementation temperature, falling within this window. This temperature strategy is the opposite of the technical concept of patent application CN114497475A, which utilizes zinc volatilization to create pores above 800°C. The latter comes at the cost of losing ZnO active sites, while this application retains ZnO active sites through low-temperature carbonization at 450-600°C. The difference in these two approaches stems from... Figure 4 The curve directly corroborates this.
[0049] The CZIF-8 / ZnO@CC prepared in the examples was used as the working electrode and assembled with the Ag / AgCl@CC reference electrode and the bare carbon cloth counter electrode to construct an electrochemical sensor.
[0050] Electrochemical active area (EASA): Calculated using cyclic voltammetry curves at different scan rates and the Randles-Sevcik equation, the EASA of CZIF-8 / ZnO@CC is 4.48 cm⁻¹. 2 The 3.55 cm⁻¹ of CZIF-8@CC prepared in the comparative example was significantly higher. 2This indicates that the flower-like zinc oxide framework effectively inhibits the aggregation of ZIF-8 particles. The charge transfer resistance (Rct) of the CZIF-8 / ZnO@CC composite electrode material obtained in the example is 4.3 Ω.
[0051] Using the same method, the electrochemical performance of the ZIF-8 / ZnO@CC (flower-like) obtained in step S3 of Example 1 was tested. The charge transfer resistance (Rct) was 11.31 Ω, and the electrochemical active surface area (EASA) was 1.72 cm². 2 The morphology of zinc oxide was screened; spherical zinc oxide exhibited a charge transfer resistance (Rct) of 28.35 Ω and an electrochemically active area of 0.84 cm². 2 .
[0052] The preparation method of spherical zinc oxide is as follows: Using a PT-CC electrode as the working electrode, an Ag / AgCl electrode as the reference electrode, and a platinum electrode as the counter electrode, electrodeposition was performed at a constant potential of -1.0 V (vs. Ag / AgCl) for 600 s in an electrolyte containing 5 mM Zn(NO3)2·6H2O and 0.1 M KNO3, at an electrolyte temperature of 70°C. After deposition, the surface was rinsed with deionized water and dried at 50°C to obtain carbon cloth with spherical zinc oxide loaded on its surface.
[0053] Nitrite detection performance: In 0.1 M PBS (pH 7.5) containing 1 mM nitrite, the oxidation peak current density of CZIF-8 / ZnO@CC was significantly higher than that of CZIF-8@CC. The chronoamperometric method (0.95 V, vs. Ag / AgCl) showed a linear range of 1–8330 μM and a sensitivity of 4406 μA mM. -1 cm -2 The limit of detection (LOD) was 0.24 μM.
[0054] Sulfite detection performance: In 0.1 M PBS (pH 7.5) containing 2 mM sulfite, CZIF-8 / ZnO@CC also exhibited excellent electrocatalytic activity. Chronoamperometric determination (0.50 V, vs. Ag / AgCl) showed a linear range of 2–8330 μM and a sensitivity of 3061 μA mM. -1 cm -2 The detection limit was 0.52 μM.
[0055] The it curves of nitrite (a) and sulfite (d) at different voltages for the CZIF-8 / ZnO@CC electrode are shown below. Figure 8 .
[0056] Selectivity: In the presence of interfering substances such as 200 μM urea, ZnSO4, NaCl, and glucose, the sensor's response to 20 μM nitrite and 50 μM sulfite is almost unaffected, indicating excellent anti-interference ability.
[0057] Reproducibility and stability: The relative standard deviations (RSDs) of the response current densities of the five independently prepared electrodes to nitrite and sulfite were less than 1.730% and 2.767%, respectively; the RSDs of the long-term stability test over 5 weeks were less than 2.762% and 2.785%, respectively.
[0058] Actual sample testing: A portable electrochemical sensor was constructed by integrating CZIF-8 / ZnO@CC with a USB-type micro workstation and mobile terminal application to detect nitrite and sulfite in sausages, kimchi, milk, and tap water. Figure 7 The recoveries of spiked nitrite were 104.73%–112.87% and 103.05%–112.42% (nitrite), respectively, consistent with the results of UV-vis spectrophotometry. See Tables 1 and 2 for details.
[0059] UV-vis spectrophotometric determination method: 1. Nitrite Determination: GB 5009.33-2025 "National Food Safety Standard - Determination of Nitrite and Nitrate in Food" 2. Sulfite determination: GB 5009.34-2022 National Food Safety Standard - Determination of Sulfur Dioxide in Food.
[0060] Table 1. Detection of nitrite in real food samples (n = 3)
[0061] Table 2. Detection of sulfites in real food samples (n = 3)
[0062] Recovery rate a = Actual measurement after spiking / (Actual measurement before spiking + Spiked) × 100% Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.
Claims
1. A ZIF-8 derived electrode material assisted by a flower-like ZnO sacrificial zinc source, characterized in that, It includes a carbon cloth substrate, a flower-shaped zinc oxide three-dimensional framework loaded on the surface of the carbon cloth, and a ZIF-8 derived amorphous carbon / zinc oxide composite layer covering the surface of the flower-shaped zinc oxide framework, wherein the amorphous carbon / zinc oxide composite layer and the flower-shaped zinc oxide framework form a hierarchical structure.
2. The method for preparing the ZIF-8 derived electrode material assisted by the flower-shaped ZnO sacrificial zinc source as described in claim 1, characterized in that, Includes the following steps: S1. Carbon cloth pretreatment: Clean the carbon cloth, dry it, and treat it with low-temperature plasma to obtain hydrophilic carbon cloth PT-CC; S2. Electrodeposition of flower-shaped zinc oxide: Using PT-CC as the working electrode, cathodic electrodeposition occurs in an electrolyte containing Zn(NO3)2·6H2O and KCl. KCl acts as a morphology guiding agent to induce the formation of flower-shaped zinc oxide structure, resulting in carbon cloth ZnO@CC with flower-shaped zinc oxide grown on the surface. S3. In-situ growth of ZIF-8: Using ZnO@CC as the working electrode, cathodic electrodeposition occurs in an electrolyte containing 2-methylimidazole and Zn(NO3)2·6H2O, and ZIF-8 is grown in-situ on the flower-shaped zinc oxide surface to obtain ZIF-8 / ZnO@CC. S4. Carbonization treatment: Under an inert atmosphere, ZIF-8 / ZnO@CC is heated to 500°C and carbonized to obtain the composite electrode material CZIF-8 / ZnO@CC.
3. The preparation method according to claim 2, characterized in that, In step S1, the process conditions for low-temperature plasma cleaning are: 60 Pa vacuum and 0.5 cm electrode spacing for 40 minutes.
4. The preparation method according to claim 2, characterized in that, In step S2, an Ag / AgCl electrode is used as the reference electrode and a platinum electrode is used as the counter electrode. The electrolyte in step S2 contains 2.5 mM Zn(NO3)2·6H2O and 5 mM KCl. Cathodic electrodeposition is performed at a constant potential of -1.1V. The electrodeposition time is 300s and the electrolyte temperature is 50℃.
5. The preparation method according to claim 2, characterized in that, In step S3, an Ag / AgCl electrode is used as the reference electrode and a platinum electrode is used as the counter electrode. The electrolyte in step S3 contains 0.4 M 2-methylimidazole and 0.05 M Zn(NO3)2·6H2O. Cathodic electrodeposition is performed at a constant potential of -1.1 V. The electrodeposition time is 30 minutes and the electrolyte temperature is room temperature.
6. The preparation method according to claim 2, characterized in that, In step S4, the heating rate is 5°C / min and the carbonization time is 30 minutes.
7. The application of the flower-shaped ZnO sacrificial zinc source-assisted ZIF-8 derived electrode material as a working electrode in an electrochemical sensor.
8. An electrochemical sensor, characterized in that, The ZIF-8 derived electrode material, which is assisted by the flower-shaped ZnO sacrificial zinc source as described in claim 1, is used as the working electrode.
9. The application of the electrochemical sensor according to claim 8 in the detection of nitrite and / or sulfite in food or tap water.
10. A method for electrochemically detecting nitrite and / or sulfite in food or tap water, characterized in that, Based on the electrochemical sensor described in claim 8, detection is performed by cyclic voltammetry, amperometric current-time method, or differential pulse voltammetry.
Citation Information
Patent Citations
Zinc-containing nitrogen-doped porous carbon-coated zinc-based negative electrode material for lithium ion battery
CN114497475A
Electrochemical self-supporting modified electrode for detecting nitrite in food
CN117269271A
